“People are having lots of other kinds of sex”: Exploring sexual lifeworlds of LGBTQ+ young people in Bangladesh - Prima Alam; Cicely Marston (Cogent Social Sciences)
A lack of recognition of sexual diversity in Bangladesh continues to contribute to a scarcity in in-depth research around lived experiences of sexual and gender diverse young people. In this article, we adapt a phenomenological reflective lifeworld approach to capture the essential aspects of sexual intimacy as described by diverse young people. This article is based on qualitative data collected in Dhaka, Bangladesh over nine months in 2019 as part of the first author’s doctoral research. Using thematic analysis, we draw on experiences of normative sexual expectations from biographical in-depth interviews with 14 self-identifying lesbian, gay, bisexual, transgender, queer, and others (LGBTQ+) individuals aged 18 to 24 years. According to participants, sexual intimacy as experienced by LGBTQ+ young people in Bangladesh meant desiring consensual sexual and romantic relationships with sexually “matched” partner(s) while navigating heteropatriarchal sexuality norms. We observed five interlinked themes which encompassed the sexual lifeworld of young people in our study: desire for romantic intimacy in sexual interactions; need for discretion when navigating sex and relationships; “matching” sexual roles in partnerships; challenges to relational power dynamics of masculinity; and embodying notions of sexual morality. Our findings captured the essence of young people’s sexual lifeworlds in our study and indicate a universality around sexual intimacy while still making space for intersections of diverse lived experiences and social orientations. Further research is required to better understand these nuances in sexual behaviour.